(untitled) (Research, Society and Development, 2020)
This study aimed to understand the possible effects of acute thermal stress (32ºC, 12 hours) on body temperature using two measurement methods (via probe and rectal), on the morphometric aspects of the heart and aortic artery, on gene expression (superoxide dismutase, glutathione peroxidase-3, nitric oxide synthase, angiotensin-converting enzyme and esterified cholesterol transfer protein), inflammatory parameters (myeloperoxidase and N-acetylglycosaminidase), oxidative stress parameters and nitrite levels in broilers (Cobb 500) at 42 days of age. 36 broilers with 42 days of age were used, distributed in a 2x2 factorial scheme: two thermal environments (comfort at 18ºC and stress at 32ºC) and two methods of measuring body temperature (via probe and rectal). Thermal stress triggered an increase in body temperature regardless of the measurement method. There was a significant effect on the thickness of the aortic artery wall and on the lateral lateral and posterior antero diameters (P <0.05). Likewise, there was a difference in the dosages of lipid hydroperoxides, in the quantification of reactive oxygen species and in the dosage of nitrite (P <0.05). The quantification of the mRNA of the induced nitric oxide synthase, angiotensin-converting enzyme and esterified cholesterol transfer protein genes were significantly higher in animals subjected to heat stress. Thus, it can be concluded that acute thermal stress was able to promote several morphological and molecular changes in the heart and aorta artery of broilers.